Competitive Strategy For a Niche Oilfield Service Company in Indonesia: a Case Study of Vikingr - Danial Wildansyah; Gallang Perdhana Dalimunthe (Journal of Accounting and Finance Management, 2026)
Indonesia’s upstream oil and gas industry is maturing, making well intervention and plug-and-abandonment central to sustaining production. Between 2025 and 2030 the country may see roughly 16,143 intervention and 2,340 plug-and-abandonment activities, with cumulative spend near US$616 million and US$398 million, while a one-million barrel-per-day production target and local-content thresholds of 55 to 75 percent reshape competition. This study asks how Vikingr, a Scandinavian niche specialist operating in Indonesia, can expand and sustain growth in this market. Using an instrumental single-case study with three semi-structured interviews of senior operator decision-makers and triangulated secondary data, the analysis applies the focus strategy, the resource-based view, supplier-selection theory and the Strategy Diamond, supported by environmental, industry, segmentation and synthesis frameworks. The most defensible position is operational problem-solving with specialized well-barrier and abandonment tools; technical capability alone is insufficient, as trust depends on documented performance, transparent communication, early engagement and assurance documentation. The proposed strategy is a phased Defend, Deepen and Diversify roadmap built on fit-for-purpose tools, an assurance pack and risk-adjusted value pricing. The contribution is contextual and managerial rather than theoretical.